Исследование алгоритмов сжатия графической и видеоинформации с целью использования в мультимедийных программных применениях - Черепахин, В. М.; Островной, П. П. (Eastern-European Journal of Enterprise Technologies, 2009)
A research object are algorithms of compression of graphic and video-information. The purpose of work are researches of algorithms of compression of graphic and video-information with the purpose of the use in multimedia applications, and also use of different types of images filtration for the improvement of their quality after application to them of wave algorithm of compression.